2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037752
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost video-oculography system for vestibular function testing

Abstract: In order to remain in focus during head movements, vestibular-ocular reflex causes eyes to move in the opposite direction to head movement. Disorders of vestibular system decrease vision, causing abnormal nystagmus and dizziness. To diagnose abnormal nystagmus, various studies have been reported including the use of rotating chair tests and videonystagmography. However, these tests are unsuitable for home use due to their high costs. Thus, a low-cost video-oculography system is necessary to obtain clinical fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…9 shows the latencies measured in the vertical tests while (8) shows the linear estimation of the values (going toward the stimulus and going back to the center of the screen). Comparing (7) with (8), the behavior of latencies in healthy volunteers seems to be analogous: linear increase and a higher slope with the age in the returning saccades.…”
Section: A Visually Guided Sacadde Testmentioning
confidence: 88%
See 3 more Smart Citations
“…9 shows the latencies measured in the vertical tests while (8) shows the linear estimation of the values (going toward the stimulus and going back to the center of the screen). Comparing (7) with (8), the behavior of latencies in healthy volunteers seems to be analogous: linear increase and a higher slope with the age in the returning saccades.…”
Section: A Visually Guided Sacadde Testmentioning
confidence: 88%
“…8 presents the mean values of the horizontal latency during the test (go to the stimulus and back to the center). Using a linear estimation model to evaluate the progression of the values, it is observed that the latency of saccadic movement is higher with aging in both, horizontal and vertical movements (7).…”
Section: A Visually Guided Sacadde Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al, en el año 2017 13 desarrolló un video oculográfico de bajo coste. Es un aparato que es capaz de detectar los movimientos sacádicos.…”
Section: Discussionunclassified